2017
DOI: 10.1177/1753193417690473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of normal trapeziometacarpal joint alignment

Abstract: The purpose of this study was to determine the alignment of the normal trapeziometacarpal joint and any changes in its alignment with age. Radial, dorsal and dorsoradial subluxation were measured on computerized tomographic scans in 50 joints of 50 adults aged 18 to 62. There were statistically significant correlations between increasing age and dorsoradial subluxation but no significant correlation with dorsal and radial subluxation. Significant dorsoradial subluxation occurs after 46 years of age in the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…They reported dorsoradial subluxation increased with age and that a value of 21% (range 14% to 30%) can be considered normal in patients older than 46 years. Direct comparisons with our findings are challenging, because although Rust et al [33] acquired CT images, their analysis was limited to 2D slices, it depended on manually selected articular landmarks, and their denominator for computing the percentage of subluxation was not rigorously described. Nevertheless, the trends in these studies are similar to our findings.…”
Section: Discussionmentioning
confidence: 87%
“…They reported dorsoradial subluxation increased with age and that a value of 21% (range 14% to 30%) can be considered normal in patients older than 46 years. Direct comparisons with our findings are challenging, because although Rust et al [33] acquired CT images, their analysis was limited to 2D slices, it depended on manually selected articular landmarks, and their denominator for computing the percentage of subluxation was not rigorously described. Nevertheless, the trends in these studies are similar to our findings.…”
Section: Discussionmentioning
confidence: 87%
“…A standard CT coronal or sagittal slice of the TMJ that uses the plane of the wrist or forearm for its alignment will result in an inaccurate measure of TMJ alignment. The true plane of the TMJ can be determined by first identifying the ‘four-corner view’ from specifically oriented axial slices through the TMJ when the two distal apices of the trapezium and the two proximal apices of the metacarpal are in view (Rust et al., 2017) (Figure 3). The coronal and sagittal planes are then aligned perpendicular to this specific axial plane and when correctly oriented, the two apices of the trapezium lie in the coronal plane of the TMJ and the two apices of the metacarpal lie in the sagittal plane.…”
Section: Measurement Of Tmj Subluxationmentioning
confidence: 99%
“…In analysing these patients for static malalignment, it is important to remember that in the resting position of a normal thumb TMJ, there is a degree of static subluxation or 'overhang' of the metacarpal over the trapezium in the radial, dorsal and dorsoradial directions, which is expected given that the metacarpal articular surface is 33% larger than the trapezial surface (Eaton and Littler, 1973;Edmunds, 2006;Pellegrini, 2001). Rust et al (2017) found that in the normal non-symptomatic TMJ, a significant increase in dorsoradial subluxation was seen in those of 46 years of age or older (median subluxation of 21% (IQR (interquartile range) 14-30%), compared with a median subluxation of 10% (IQR 4-15%) in those aged less than 45 years. In contrast, subluxation in either the radial or dorsal directions did not alter significantly with age.…”
Section: Measurement Of Tmj Subluxationmentioning
confidence: 99%
“…Furthermore, how can we differentiate "normal" or "idiopathic" dorsoradial subluxation from traumatic origins? Rust et al found in a retrospective CT study involving 50 patients aged 18 to 62 years without CMCJ I disorders that significant increase of dorsoradial subluxation occurs after 46 years of age, and a mean dorsoradial subluxation of 21% (range 14% to 30%) can be considered normal in this age group (Case Presentation 5) [42]. Hirschmann et al noted that when using MRI the thumb should be held in the "uncomfortable" opposition in which the CMCJ I is congruent only, and so, this position allows probably the best investigation in differentiation of positionrelated subluxation from underlying post-traumatic or disease-related subluxations [43].…”
Section: Carpometacarpal Joint I (Thumb)mentioning
confidence: 99%